Peningkatan Keterampilan Menulis Siswa Kelas V SDN 03/04 Margoyoso Menggunakan Media Youtube - Haniyyah, Roikhatun; Hanik, Elya Umi (ALSYS, 2022)
This study aims to improve the writing skills of 5th grade students of SD Negeri 04 Margoyoso by using YouTube as the media. The main problem in this mini research study is that students are lazy and find difficult to write a lot because of the length of online learning due to the pandemic. It can be seen from the result of student writing, unstructured interviews, and class observations and collection of documentation. This research was carried out at SD Negeri 03/04 Margoyoso in the odd semester of the academic year 2021/2022 with the research subjects being 22 students in 5th grade. This research is a mini classaction research (CAR) conducted in two cycles. Quantitative data in the form of writing skill scores were analyzed descriptively. Students writing skills increased from the precycle score of 45.56%, increased in the first cycle of 54.55% and increased again in the second cycle of 72.73%. The succes of the learning proses can be seen in the activities of students who are enthusiastic and antusiastic about participating in learning.